Analisis Bagan Aktansial Cerita Anak Jepang Urashima Taro - Rita Susanti (Lingua Cultura, 2011)
Thisi research is a kind of a research focusing on linguistic which uses semiotic in order to find out what lies behind the content of a children’s story. The subject of this research is an ancient story of a Japanese children called mukashi banashi. It comes with the title of Urashima Taro which has been translated into Indonesia Language. Through semiotic analysis, the story may be conducted in a syntaxical and semantical way. According to syntax analysis, there are two episodes in the story. In this first episode Urashima Taro becomes the subject of the research while in the latte, the turtle is the subject. We may learn that the story plott and the flow of the story have gone through a flashback process. In the structure or “batih”, it is known that the story has a complex relationship due to its expansion plot. Based on the semantic analysis, it is also know that the main/lead character of the story is Urashima Taro and the other characters are Urashima Taro’s mother and the queen. The morale message of the whole story is dedicated to all children reading it.